The 2016 Police and Crime Commissioner elections. Issue 2 (10th April 2017) - Joyce, Peter
Abstract : Purpose: The purpose of this paper is to analyse the 2016 elections for Police and Crime Commissioners (PCCs) and to compare them with those that took place in 2012. It seeks to evaluate the background of the candidates who stood for office in 2016, the policies that they put forward, the results of the contests and the implications of the 2016 experience for future PCC elections. Design/methodology/approach: This paper is based around several key themes – the profile of candidates who stood for election, preparations conducted prior to the contests taking place, the election campaign and issues raised during the contests, the results and the profile of elected candidates. The paper is based upon documentary research, making particular use of primary source material. Findings: The research establishes that affiliation to a political party became the main route for successful candidates in 2016 and that local issues related to low-level criminality will dominate the future policing agenda. It establishes that although turnout was higher than in 2012, it remains low and that further consideration needs to be devoted to initiatives to address this for future PCC election contests. Research limitations/implications: The research focusses on the 2016 elections and identifies a number of key issues that emerged during the campaign affecting the conduct of the contests which have a bearing on future PCC elections. It treats these elections as a bespoke topic and does not seek to place them within the broader context of the development of the office of PCC. Practical implications: The research suggests that in order to boost voter participation in future PCC election contests, PCCs need to consider further means to advertise the importance of the role they perform and that the government should play a larger financial role in funding publicity for these elections and consider changing the method of election. Social implications: The rationale for introducing PCCs was to empower the public in each police force area. However, issues that include the enhanced importance of political affiliation as a criteria for election in 2016 and the social unrepresentative nature of those who stood for election and those who secured election to this office in these contests coupled with shortcomings related to public awareness of both the role of PCCs and the timing of election contests threaten to undermine this objective. Originality/value: The extensive use of primary source material ensures that the subject matter is original and its interpretation is informed by an academic perspective.